2016
DOI: 10.18632/oncotarget.9263
|View full text |Cite
|
Sign up to set email alerts
|

Combining 2-deoxy-D-glucose with fenofibrate leads to tumor cell death mediated by simultaneous induction of energy and ER stress

Abstract: Unregulated growth and replication as well as an abnormal microenvironment, leads to elevated levels of stress which is a common trait of cancer. By inducing both energy and endoplasmic reticulum (ER) stress, 2-Deoxy-glucose (2-DG) is particularly well-suited to take advantage of the therapeutic window that heightened stress in tumors provides. Under hypoxia, blocking glycolysis with 2-DG leads to significant lowering of ATP resulting in energy stress and cell death in numerous carcinoma cell types. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Inhibition of glycolysis with GW6471 has also been reported 44 . Cytotoxic effects of a combination of fenofibrate with glycolysis inhibitors have been reported and our lab discovered a similar mechanism for metformin cytotoxicity in MS1 VEGF angiosarcoma cells 17,45 . Further studies will be required to clarify the underlying mechanisms and pharmacological studies supporting PPARα- and NFκB-independence may be complemented by RNA interference (RNAi)-mediated ‘knock-down’ experiments.…”
Section: Discussionmentioning
confidence: 59%
“…Inhibition of glycolysis with GW6471 has also been reported 44 . Cytotoxic effects of a combination of fenofibrate with glycolysis inhibitors have been reported and our lab discovered a similar mechanism for metformin cytotoxicity in MS1 VEGF angiosarcoma cells 17,45 . Further studies will be required to clarify the underlying mechanisms and pharmacological studies supporting PPARα- and NFκB-independence may be complemented by RNA interference (RNAi)-mediated ‘knock-down’ experiments.…”
Section: Discussionmentioning
confidence: 59%
“…Another study also showed that Nile tilapia fed with low-energy diets (12•56 MJ/kg, 30 % protein) exhibited extremely poor growth and feed conversion efficiency with high mortality rates, compared with those fed with moderate-(16•75 MJ/kg, 40 % protein) and high-energy (20•93 MJ/kg, 50 % protein) diets (19) . Furthermore, fenofibrate was reported to exacerbate energy stress and cell death in three human tumour cell lines which had been induced energy stress by 2-deoxy-glucose (a glycolytic inhibitor) (35) . In agreement with these studies, increasing oxidative stress and HSI could further reflect the energy stress induced by fenofibrate in the low energy intake situation (LP-fed fish) (14•5 MJ/kg, Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Researches under in vitro and in vivo conditions demonstrate that concomitant use of 2-DG with inhibitors of lysosomal permeabilization increased its anti-tumor action, inducing mitochondrial damage and necrotic cell death [150]. As well, cotreatment of 2-DG with the PPARα agonist, fenofibrate (FF) leads to cancer cell death by inducing endoplasmic reticulum stress [151]. Despite these promising results, 2-DG clinical trials were stopped in phase I, since 2-DG resulted in intolerable hypoglycemia and reduced white blood cell counts in leukemia patients [152].…”
Section: Targeting Metabolism For Cancer Therapymentioning
confidence: 99%